Evaluating the Implementation of the Stunting Prevention Program at the Regional Technical Unit of Binjai Estate Health Center in Binjai City - Putranto Manalu; Margaretha Febrina Br Ginting; Ermi Girsang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Stunting remains a critical public health issue affecting the quality of human resources, particularly in Indonesia, where its prevalence remains high across various regions. According to the 2021 Indonesia Nutritional Status Survey (SSGI), the national stunting prevalence was 24.4%, with North Sumatra reporting 30.11% and Binjai City 21.7%, all of which exceed the WHO target of below 20%. These statistics underscore the urgent need for effective prevention strategies, particularly through nutritional interventions at the primary healthcare level. This study aims to evaluate the implementation of the stunting prevention program at the Regional Technical Implementation Unit of the Binjai Estate Community Health Center in Binjai City. The program components include nutrition education, regular monitoring of pregnant women and toddlers, and the provision of supplementary feeding. A qualitative descriptive approach was employed, utilizing in-depth interviews with healthcare personnel and field observations conducted in 2023. Findings indicate that although the program is generally well-implemented, several challenges persist. These include low community participation in outreach activities and persistent cultural myths that impede proper understanding of stunting. Nonetheless, there has been a noticeable increase in awareness regarding balanced nutrition among pregnant women and caregivers of toddlers. Monitoring is routinely conducted via the SIMPUS and SIP systems; however, long-term impact evaluation remains insufficient. In conclusion, while the stunting prevention program demonstrates promising outcomes, further improvements are necessary in enhancing community engagement, strengthening communication strategies, and developing a more robust evaluation system. Strengthening human resource capacity, improving inter-sectoral coordination, and expanding public access to accurate nutritional information are recommended to more effectively combat stunting Keywords: Stunting, Program Implementation, Primary Health Care, Nutrition Education, Monitoring and Evaluation